Deployment of Intelligent Transport Systems for Sustainable Transport Development - Nikolova, Hristina (Research Papers, 2017)
The paper aims at presenting the specific features of the intelligent transport systems, the impacts of the deployment of intelligent transport systems on sustainable development of transport and transport infrastructure as well as the economic effects expected from the wide deployment of these systems.Commonly adopted methods for economic impact assessment of ITS are systematized using world and European experience and expected effects and impacts on the level of sustainable transport development are described.Another important task of the paper is to represent the results the impact assessment and the results of cost – benefit analysis for different ITS – projects deployed in Bulgaria under SEE-ITS project, conducted within South East Europe Transnational Programme. The respective costs and benefits are proved to be key factors for the realization of the strategic transport infrastructure projects in Bulgaria and for the development of a framework for multi-criteria analysis for ITS deployment projects.The conclusions describe the key issues in the ITS impact assessment and clarify their contribution to the sustainable transport development.